2017
DOI: 10.1002/app.45204
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric and thermal behaviors of fluorine‐containing dianhydride‐modified polybenzoxazine: A molecular design flexibility

Abstract: Fluorine-containing copolybenzoxazines were successfully prepared by reacting bisphenol-AF/aniline-based benzoxazine resin (BAF-a) with 4,4 0 -(hexafluoroisopropylidene) diphthalic anhydride (6FDA) in N,N-dimethylacetamide solvent. The dielectric and thermal properties as well as flexibility of the resulting copolymer films were investigated. The incorporation of fluorine groups into polybenzoxazine was found to substantially decrease the dielectric constant of the resulting copolybenzoxazine to as low as 2.6.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Thermosetting and thermoplastic materials containing fluorine were designed and prepared. The researchers investigated various kinds of benzoxazine resins containing fluorinated groups such as bisphenol-AF [20], 1,4-tetrafluorobenzene or 4,4-octafluorobiphenylene dioxyphenylene [21,22] in molecular chains. The results indicated that the introduction of fluorine can serve the reducing of dielectric constants and dielectric loss.…”
Section: Introductionmentioning
confidence: 99%
“…Thermosetting and thermoplastic materials containing fluorine were designed and prepared. The researchers investigated various kinds of benzoxazine resins containing fluorinated groups such as bisphenol-AF [20], 1,4-tetrafluorobenzene or 4,4-octafluorobiphenylene dioxyphenylene [21,22] in molecular chains. The results indicated that the introduction of fluorine can serve the reducing of dielectric constants and dielectric loss.…”
Section: Introductionmentioning
confidence: 99%
“…The absorption band at 1597 cm −1 and 1398 cm −1 were corresponding to −C=N and −C−N of pyrimidine ring, respectively, and the signal of −C−O−C− appeared at 1276 cm −1 [18] . While the absorption peak at 2974 cm −1 belonged to −C−H for PBAD and PBAD‐1, the characteristic absorption signal of −C−F for PBFD, PBFD‐1 and PBFD‐2 appeared at 1172 cm −1 [19] . During the curing process, the cyano groups on the monomers were cross‐linked to form polyindoline, polytriazine and phthalocyanine structures, which were detected at 1730 cm −1 , 1357 cm −1 , 1012 cm −1 , respectively, indicating the successful synthesis of PBPD‐1 and PBPD‐2 [20] .…”
Section: Resultsmentioning
confidence: 97%
“…[18] While the absorption peak at 2974 cm À 1 belonged to À CÀ H for PBAD and PBAD-1, the characteristic absorption signal of À CÀ F for PBFD, PBFD-1 and PBFD-2 appeared at 1172 cm À 1 . [19] During the curing process, the cyano groups on the monomers were cross-linked to form polyindoline, polytriazine and phthalocyanine structures, which were detected at 1730 cm À 1 , 1357 cm À 1 , 1012 cm À 1 , respectively, indicating the successful synthesis of PBPD-1 and PBPD- 2. [20] Compared with the spectra of monomer PBPD, the absorption peak at 2231 cm À 1 of PBPD-1 and PBPD-2 were significantly weakened but still remaining, which might be due to the large volume of the polytriazine ring impeded the further reaction of cyano groups.…”
Section: Ft-ir Analysis Of Monomers and Polymersmentioning
confidence: 99%
“…Both degradation temperatures are considered quite high. The char yield, on the other hand, is very low for benzoxazines, particularly for those containing a CF 3 group, which is typically in the range of 36–68% [ 7 , 11 , 12 , 17 , 19 , 23 , 23 , 27 , 34 ], or a furan group, which is typically between 30–74% due to high crosslinking capabilities [ 41 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ]. The char yield at 800 °C was approximately 24%, which is unexpectedly low for a benzoxazine such as BAF-oda-fu, which contains both above functionalities.…”
Section: Resultsmentioning
confidence: 99%
“…The synthesis of fluorinated benzoxazines requires rather different conditions from the ordinary, non-fluorinated benzoxazines due in part to the strong electron-withdrawing tendency of the CF group. Fluorinated benzoxazines have been reported in the literature [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. Polybenzoxazines derived from fluorinated monomers are studied for their special synthesis methods [ 8 , 15 , 23 ], low dielectric constant properties [ 9 , 10 , 19 , 27 , 29 , 32 , 34 ], structure–property relationships [ 7 , 11 , 28 , 30 ], fuel cell applications [ 13 ], low surface free energy or superhydrophobicity [ 12 , 14 ], and high thermal properties [ 16 , 17 , 18 ,…”
Section: Introductionmentioning
confidence: 99%